2014
DOI: 10.1001/jamaneurol.2014.1358
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Brain Amyloid Detection in Clinical Practice Using Cerebrospinal Fluid β-Amyloid 42

Abstract: IMPORTANCE Before adding cerebrospinal fluid (CSF) biomarkers to the diagnostic workup of Alzheimer disease, it needs to be determined whether CSF biomarkers analyzed in routine clinical practice can reliably predict cortical β-amyloid (Aβ) deposition. OBJECTIVES To study whether CSF biomarkers, analyzed consecutively in routine clinical practice during 2 years, can predict cortical Aβ deposition and to establish a threshold for Aβ42 abnormality. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
322
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 330 publications
(353 citation statements)
references
References 50 publications
23
322
4
4
Order By: Relevance
“…The use of amyloid-PET positivity as a standard of truth overcomes this problem. A previous study 27 also found a higher CSF Ab 42 cutpoint based on amyloid-PET compared with routinely used cutpoints, although our cutpoint of 557 pg/mL was lower than in the previous study. It should be noted that the present study addressed data derived from 5 different laboratories, while in particular Ab 42 is sensitive to preanalytical and analytical factors with interlaboratory variability up to 28%.…”
Section: Concordance Between Csf Ab 42 and Amyloid-petcontrasting
confidence: 86%
“…The use of amyloid-PET positivity as a standard of truth overcomes this problem. A previous study 27 also found a higher CSF Ab 42 cutpoint based on amyloid-PET compared with routinely used cutpoints, although our cutpoint of 557 pg/mL was lower than in the previous study. It should be noted that the present study addressed data derived from 5 different laboratories, while in particular Ab 42 is sensitive to preanalytical and analytical factors with interlaboratory variability up to 28%.…”
Section: Concordance Between Csf Ab 42 and Amyloid-petcontrasting
confidence: 86%
“…CSF Aβ42 levels correlate inversely with neuropathological measures of plaque density in Alzheimer brains [3,4] and show high concordance with amyloid positron emission tomography [5,6]. Routine clinical use of CSF Aβ42 is part of the diagnostic process in an increasing number of countries and may be used as a surrogate for neuropathology to either support or rule out a diagnosis of AD in memory-impaired individuals [4,[6][7][8]. Together with other markers, Aβ42 is included in both the IWG-2 and the NIA-AA research criteria for AD [9][10][11].…”
Section: Introductionmentioning
confidence: 93%
“…It is used to aid in early clinical diagnosis, for enrichment purposes in clinical trials, to monitor the effect of therapeutics and for research purposes [1,2]. CSF Aβ42 levels correlate inversely with neuropathological measures of plaque density in Alzheimer brains [3,4] and show high concordance with amyloid positron emission tomography [5,6]. Routine clinical use of CSF Aβ42 is part of the diagnostic process in an increasing number of countries and may be used as a surrogate for neuropathology to either support or rule out a diagnosis of AD in memory-impaired individuals [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that to reliably use biomarkers for all of these purposes and also to be able to compare research findings across the community a lot of effort is being put into reducing measurement variability between different centers by investigating confounding factors. 49,62,63 There are some drawbacks of the study such as potential cohort effects, drop-outs, low number of cases that has developed specific dementia diseases, the presence of lacunes has not been rated in the diagnostic process, and that for practical reasons not all patients eligible for inclusion have been included in the study. Time constraints in the clinic may be a contributing factor to noninclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The CSF biomarker analyses are performed by board-certified laboratory technicians using a standard laboratory quality control program to assure quality, as described previously. 49 The core biomarker levels are mainly evaluated by commercially available enzyme-linked immunosorbent assays (INNOTEST, Fujirebio, Gent, Belgium). 50,51,52 Internal quality controls, two or more internal control CSF samples (aliquots of pooled CSF), are analyzed each run, to minimize between-assay variability.…”
Section: Cerebrospinal Fluid Markersmentioning
confidence: 99%